2005
DOI: 10.1111/j.1471-0528.2005.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of maternal ischaemic heart disease after gestational hypertensive disease

Abstract: aObjective The aim of this study was to investigate whether the risk of developing ischaemic heart disease (IHD) later in life increases with severity and recurrence of gestational hypertensive disease. Design Cross-sectional population-based study.Setting Sweden.Population Women (403,550) giving birth to their first child in Sweden, 1973Sweden, -1982. Of this cohort, 207,054 women who also gave birth to a second child during the same period were analysed separately. Methods All women were followed up for 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
167
2
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(192 citation statements)
references
References 33 publications
17
167
2
6
Order By: Relevance
“…The role of GH combined with SGA and/or preterm delivery on future CVD has been addressed in a few studies 5, 20, 24, 28. These studies support our findings, but have limitations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The role of GH combined with SGA and/or preterm delivery on future CVD has been addressed in a few studies 5, 20, 24, 28. These studies support our findings, but have limitations.…”
Section: Discussionsupporting
confidence: 78%
“…A possible relationship between GH and risk of maternal CVD has been studied to a much smaller extent. While several studies have reported a significant association between GH and subsequent CVD,5, 19, 20, 23, 24, 25, 26, 27, 28, 29, 30 only 4 of these had a comparable cohort size and a similar follow‐up time compared with our study 19, 20, 23, 29. None of these studies looked at the combined effects of GH, SGA infant, preterm delivery, and parity as predictors of subsequent CVD.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition to the severity of preeclampsia, recurrent preeclampsia and preeclampsia superimposed on chronic hypertension are also associated with additional increases in CVD risk 48, 49, 50. Women with recurrent preeclampsia have a higher incidence of cardiovascular hospitalization (281.4 versus 167.7 per 1000 women) and a shorter time to first cardiovascular event (12.7 versus 11.6 years) compared with women who experienced preeclampsia in only 1 pregnancy 49.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdmentioning
confidence: 99%
“…The risk of future CVD with GH has generally been found to be lower than that associated with preeclampsia38, 46, 50; however, some recent studies have actually identified a higher risk of CVD associated with GH. A study of a Finnish cohort with 39 years of follow‐up found that GH was associated with modestly higher CVD risk than preeclampsia (HR: 1.45 versus 1.40) 44.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdmentioning
confidence: 99%